12=6.25+.75x

Simple and best practice solution for 12=6.25+.75x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 12=6.25+.75x equation:


Simplifying
12 = 6.25 + 0.75x

Solving
12 = 6.25 + 0.75x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.75x' to each side of the equation.
12 + -0.75x = 6.25 + 0.75x + -0.75x

Combine like terms: 0.75x + -0.75x = 0.00
12 + -0.75x = 6.25 + 0.00
12 + -0.75x = 6.25

Add '-12' to each side of the equation.
12 + -12 + -0.75x = 6.25 + -12

Combine like terms: 12 + -12 = 0
0 + -0.75x = 6.25 + -12
-0.75x = 6.25 + -12

Combine like terms: 6.25 + -12 = -5.75
-0.75x = -5.75

Divide each side by '-0.75'.
x = 7.666666667

Simplifying
x = 7.666666667

See similar equations:

| -2-3y=3 | | 5x^2+13x=13 | | 50x^2-52x=0 | | -v+5(6+5v)=126 | | 6x-25=-1 | | 6x+-25=-1 | | (5t-3)(t+5)=0 | | 3x^2-2x-3-8x+6-x^2= | | 6x+30=20x+10 | | 4/5x•-4/5 | | 7=n/12 | | x+(2x+250)=2858 | | 4/5x×-5/4 | | 8(r)=13 | | 2x+16=9-25 | | (cos)(x)=0 | | 12x^2+46x-42=0 | | 4/5x-4/5 | | 3.5x-2=-9 | | cos(2x)+2cos(4x)=cos(6x) | | 3x+6+2x+4=90 | | 3(-6m+3)=99 | | (x^2+4x+8)(2x-1)= | | -3f/5-4/15 | | 4u+8=7 | | x=(-11)-(-21) | | 3x+6+2x=90 | | 39+d=100 | | 4xy+-9xy-3xy= | | 3x+x+7=15 | | T-5/7=5/8 | | 8w+16-2=8x+38 |

Equations solver categories